Visible light induced enhanced photocatalytic degradation of industrial effluents (Rhodamine B) in aqueous media using TiO2 nanoparticles - Carneiro, Joaquim A. O. (2016)
In recent years, new textile materials have been developed through the use of nanotechnology-based tools. The development of textile surfaces with self-cleaning properties has a large combined potential to reduce the environmental impact related to pollution. In this research work, three types of textiles substrates (cotton, Entretela, and polylactic acid (PLA)) were functionalized with titanium dioxide nanoparticles (TiO2) using chemical and mechanical processes (padding). During the functionalization process, two different methods were used, both of which allowed a good fixation of nanoparticles of TiO2 on textile substrates. The samples were examined for morphology and for photocatalytic properties under visible light irradiation. A study aimed at evaluating the effect of pH of the aqueous solution of TiO2 nanoparticles was performed in order to promote interaction between TiO2 and the dye solution rhodamine B (Rh-B). The TiO2 nanoparticles were characterized by X-ray diffraction (XRD). The measurement of the zeta potential of the TiO2 nanoparticle solution proved to be always positive and have low colloidal stability. Chromatography (HPLC and GC-MS) analyses confirmthat oxalic acid is the intermediate compound formed during the photodegradation process.